Polyamine metabolism in flax in response to treatment with pathogenic and non–pathogenic Fusarium strains - Wojtasik, Wioleta; Kulma, Anna; Namysł, Katarzyna; Preisner, Marta; Szopa, Jan (Frontiers in Plant Science, 2015)
Flax crop yield is limited by various environmental factors, but the largest crop losses worldwide are caused by Fusarium infection. Polyamines are one of the many metabolites possibly involved in the plant response to infection. However, in flax the polyamine composition, genes involved in polyamine synthesis, and their regulation, were previously unknown. The aim of this study was to investigate the polyamine synthesis pathway in flax and its involvement in response to pathogen infection. It is well established that polyamines are essential for the growth and development of both plants and fungi, but their role in pathogen infection still remains unknown. In our study we correlated the expression of genes involved in polyamine metabolism with the polyamine levels in plant tissues and compared the results for flax seedlings treated with two pathogenic and one non-pathogenic strains of Fusarium. We observed an increase in the expression of genes participating in polyamine synthesis after fungal infection, and it was reflected in an increase of polyamine content in the plant tissues. The highest level of mRNA was characteristic for ornithine decarboxylase during infection with all tested Fusarium strains and the arginine decarboxylase gene during infection with the pathogenic strain of F. culmorum. The main polyamine identified in the flax was putrescine, and its level changed the most during infection. Moreover, the considerable increase in the cell wall-bound polyamines compared to the levels of free and conjugated polyamines may indicate that their main role during pathogen infection lies in strengthening of the cell wall. In vitro experiments showed that the polyamines inhibit Fusarium growth, which suggests that they play an important role in plant defence mechanisms. Furthermore, changes in metabolism and content of polyamines indicate different defence mechanisms activated in flax in response to infection by pathogenic and non-pathogenic Fusarium strains.